Nanoparticles-constructed spinel ZnFe2O4 anode material with superior lithium storage performance boosted by pseudocapacitance. (August 2018) - Yao, Jinhuan; Zhang, Yufang; Yan, Jing; Bin, Huang; Li, Yanwei; Xiao, Shunhua
Graphical abstract: Highlights: Nanoparticles-constructed ZnFe2 O4 was fabricated by co-precipitation method. The ZnFe2 O4 sample shows excellent high rate capability and cycling stability. The lithium storage mechanism was analyzed by CV and EIS measurements. Pseudocapacitive effect has a significant contribution to the total stored charge. Abstract: The practical application of ZnFe2 O4 in lithium ion batteries (LIBs) is severely hampered by its fast capacity fading and poor rate performance. To overcome these issues, herein, ZnFe2 O4 powders consist of aggregated nanoparticles (50∼100 nm) with porosity were prepared by a facile co-precipitation method and subsequent thermal decomposition. When used as anode material for LIBs, the ZnFe2 O4 sample delivers capacities of 920, 820, 650, 485, and 421 mA h g −1 at current densities of 0.5, 1, 3, 7, and 10 A g −1, respectively. Moreover, the sample can maintain a capacity of 814 mA h g −1 even after 300 cycles at the current density of 1 A g −1, implying an excellent rate capability and cycling stability. Cyclic voltammetry analysis reveals that both diffusion-controlled lithium storage and surface pseudocapacitive lithium storage contribute to the total stored charge of ZnFe2 O4, which boosts the high rate capability and superior cycling stability of the ZnFe2 O4 .